DISPARITAS PIDANA TERHADAP PENERAPAN PASAL 132 MENGENAI PERMUFAKATAN JAHAT NARKOTIKA GOLONGAN I (Analisis Putusan Nomor: 19/Pid.Sus/2017/PN.Swl dan Nomor: 5/Pid.Sus/2018/PN.Swl) - Al Indra (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Disparities in punishment are often related to the independence of judges becausethe punishment model set forth in the Criminal Code only formulates maximum criminalsanctions only, in addition because Law Number 48 Year 2009 on Judicial Power alsoprovides that: The judge must also consider the good and evil nature of the defendant. Thedisparity of the decision of this judge occurred also in the District Court of Sawahlunto onthe case of narcotic criminal acts which examine and decide the case of narcotics crimewith the same panel of judges and the indictment of the same article but the decision givento the defendant varies.